PRAKTEK TERBAIK BISNIS ETIS MENINGKATKAN KINERJA BISNIS PADA PERUSAHAAN PUBLIK DI INDONESIA - Indarto Indarto (Jurnal Dinamika Sosial Budaya, 2016)
This study  explored the application of business ethics in public companies in Indonesia. This research is important because the company has a moral responsibility to all its stakeholders. Companies must run their business by always using morals and ethics even though the goal is to make a profit. The research method used in this research is deskrtiptif explorative. The data used in this study is the primary data which obtained through questionnaires with open questions. The population in this study is a public company listed on the Indonesia Stock Exchange. The sampling method used is random sampling by sending a random questionnaire to a public company listed on the Indonesia Stock Exchange. The questionnaire was sent by email aimed at corporate secretary of each company. It collected 31 questionnaires that can be analyzed. The results show that public companies have been good enough in running ethical business best practices. Most of the respondents stated that business practices conducted by adhering to morals and ethics have resulted in satisfactory business performance.